2015
DOI: 10.5304/jafscd.2015.052.011
|View full text |Cite
|
Sign up to set email alerts
|

"La misma realidad de cada lugar es diferente" ("The same reality of each place is different"): A Case Study of an Organic Farmers Market in Lima, Peru

Abstract: Studies of alternative food networks have proliferated in Europe and North America while relatively little attention has been paid to similar networks in the global South. An organic farmers market in Lima, Peru, serves as a case study to examine developments in the domestic market for organic produce in Peru. Drawing from interview data and participant observations with pioneering organic farmers and nongovernmental organizations (NGOs) affiliated with the farmers market, this paper investigates how the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…The four main kinds of benefits reported by vendors in both Suva and Brooklyn are generating income, autonomy, respect, and social connectedness. These social and economic benefits also mirror those identified in previous research conducted with markets in the Global North, such as in a study with farmers selling in upstate New York (Griffin & Frongillo, 2003), and the Global South, such as in Chiapas, Mexico, and Lima, Peru (Bellante, 2017;Cody, 2015b). As noted, not all participating vendors in Suva reported that the market garnered them respect.…”
Section: Discussionsupporting
confidence: 73%
“…The four main kinds of benefits reported by vendors in both Suva and Brooklyn are generating income, autonomy, respect, and social connectedness. These social and economic benefits also mirror those identified in previous research conducted with markets in the Global North, such as in a study with farmers selling in upstate New York (Griffin & Frongillo, 2003), and the Global South, such as in Chiapas, Mexico, and Lima, Peru (Bellante, 2017;Cody, 2015b). As noted, not all participating vendors in Suva reported that the market garnered them respect.…”
Section: Discussionsupporting
confidence: 73%